An integrated palaeoenvironmental record of Early Modern occupancy and land use within Angkor Thom, Angkor. (1st January 2021) - Hall, Tegan; Penny, Dan; Vincent, Brice; Polkinghorne, Martin
Abstract: Exploring severe social, political, or economic change in past societies can reveal adaptive pathways and strategies that may be of value to contemporary society as we prepare to adapt to this century of disruption. Episodes of large-scale transformation in past societies are often framed as 'collapse' – as terminal events instigated by one or more stressors. The focus on cataclysmic episodes, often related to climatic forcing, has meant that the nuance of adaptation is not well documented in historical and archaeological records, in part due to the historical lacuna that may follow periods of social disruption. Here we present a multi-proxy record of landscape and land use change from Angkor, the administrative and ceremonial core of the Angkorian kingdom in ancient Cambodia, through a period of severe climate stress and political transition in the 14th-15th centuries to the present-day. Analysis of proxy data, including geochemistry, palynology, sedimentology, and fire history, reveal a prolonged period of land use attenuation beginning in the early to mid-14th century, interrupted by a brief increase in burning and cultivation that may represent a short period of reoccupation in the mid-16th century. Agricultural activity continued to decline, despite continuing ritual activity within the site of Angkor Thom and ongoing occupation at temple sites in the Greater Angkor region, until the 17th century when metrics for secondary forest growth and landscape recovery reached consistently high levels. These results provide further evidence exposing the varied trajectories of occupation across key Cambodian urban centres, and contribute to the developing narrative of Angkor as a city that underwent transformation, rather than collapse, between the Angkorian (c. 800- c. 1450 C.E.) and Early Modern (c. 1450 - c. 1850 C.E.) periods. Highlights: Records of landscape change contextualise cultural evidence of societal transition. Narratives that extend beyond disruption can reveal examples of social resilience. Angkor's evolution from the Angkorian to Early Modern Periods was spatially complex. Angkor Thom's population fell from the 14th C. but the city endured as a sacred district.